2009
DOI: 10.1063/1.3068622
|View full text |Cite
|
Sign up to set email alerts
|

Graded permanent magnets

Abstract: The effect of semihard magnetic phases and interfaces on the performance of nanostructured two-phase permanent magnets is investigated by model calculations. In addition to the trivial coercivity increase due to the replacement of soft regions by semihard regions, there is a coercivity enhancement even if the volume-averaged anisotropy is kept constant during the introduction of the semihard phase. A variational approach is used to derive analytical results for representative anisotropy profiles. The improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The above results based on renewed modelling and experimental works have shown that a well-chosen soft phase and engineered interface will further enhance the energy product of a nanocomposite hard/soft magnet. Recent theoretical studies by Skomski [71], by Sato et al [72] and by Xia [73] on nanocomposite magnets have considered effects of 'semi-hard phase' and orientation of the grains on the interphase exchange coupling. Those factors were largely neglected in the early modelling work.…”
Section: Exchange-coupled Nanocomposite Magnets-a Fundamental Point Omentioning
confidence: 99%
“…The above results based on renewed modelling and experimental works have shown that a well-chosen soft phase and engineered interface will further enhance the energy product of a nanocomposite hard/soft magnet. Recent theoretical studies by Skomski [71], by Sato et al [72] and by Xia [73] on nanocomposite magnets have considered effects of 'semi-hard phase' and orientation of the grains on the interphase exchange coupling. Those factors were largely neglected in the early modelling work.…”
Section: Exchange-coupled Nanocomposite Magnets-a Fundamental Point Omentioning
confidence: 99%
“…Together with Mn-Al and Mn-Bi alloys, the Mn-Ga alloys are scrutinized for use as hard magnetic materials [9]. Having a low remanent magnetization and high material cost, Mn 3 Ga alone is not suitable for permanentmagnet applications, but it is a valid candidate for the hard component of an exchange spring magnet [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, from the application standpoints, we can consider functionalities for these arrays of NiCu ANWs in two-phase nanomagnets as well as the nanoscale MR and thermoelectric device applications. 27,48,49 On the other hand, thermal annealing leads to a decrease in the Hc FORC corresponding to the hard phase (from 900 to 800 Oe) as well as in the density of the soft phase from 1.88 Â 10 À6 to 1.40 Â 10 À6 (see Fig. 10).…”
Section: Resultsmentioning
confidence: 99%